Pneumococcal vaccination coverage among US adults enrolled in Medicaid and newly diagnosed with underlying medical conditions - Junqing Liu; Kelly D. Johnson; Linda Shoener Dunham (Taylor & Francis Group, 2023)
Background Adults with chronic or immunocompromising conditions have an elevated risk of invasive pneumococcal disease, yet their pneumococcal vaccination rates remain low. Methods This retrospective cohort study used the IBM MarketScan® Multi-State Medicaid database to examine pneumococcal vaccination uptake among adults 19-64 years of age with underlying conditions. Gompertz accelerated failure time model was used to examine factors associated with vaccination. Results In the study population of 108,159 adults, the vaccination rate was 4.1% after 1 year of follow-up and 19.4% after 10 years. The mean time from initial diagnosis to vaccination was 3.9 years. Adults aged 35-49 and 50-64 years (relative to 19-34) or those receiving an influenza vaccination were more likely to receive a pneumococcal vaccination. Adults with HIV/AIDS were more likely, while adults with chronic heart or lung disease, alcohol or tobacco dependence, or cancer were less likely to be vaccinated than adults with diabetes mellitus. Adults diagnosed by specialists were less likely to be vaccinated than those diagnosed by primary care providers. Conclusions The rates of pneumococcal vaccination among adults with Medicaid plans and underlying conditions were well under Healthy People Initiative targets. Insights into factors associated with vaccination can inform efforts to improve vaccination rates among this population.